Analysis and synthesis of existing procedures used to determine the reuse potential of building elements - Barbara Lambec; Maléna Bastien-Masse; Corentin Fivet (Frontiers in Built Environment)
Amid escalating concerns over CO2 emissions, resource depletion, and waste generation in construction, reusing building elements from obsolete structures presents a sustainable solution. This paper critically reviews 21 procedures used in Europe and the United States (2001–2021) for identifying and evaluating reusable elements prior to transformation projects. Developed by various stakeholders with differing goals, these procedures propose diverse approaches. The study provides a comprehensive overview of their purposes, evaluation criteria, data requirements, and timeframes. Comparative analysis reveals subjectivity in data inputs and a lack of consensus on the comprehensiveness required for effective evaluation. To move from recycling to reuse, the criteria must expand to include projective values, deconstruction processes, and second-use planning. These aspects are essential for assessing the availability, deconstruction, and reuse potential of building elements. The findings offer key insights for developing standardized, adaptable, and automatable assessment procedures that can facilitate efficient and effective reuse practices in future projects.